Perencanaan Merdeka Belajar Berbasis Literasi Pada Pembeajaran IPA di SMP Negeri 12 Sijunjung - Yenny Septi; Sirajul Munir; M Haviz (IAIN Batusangkar, 2021)
Literacy-based independent learning planning is important to be applied in the science learning process. The principal as the manager of SMP Negeri 12 Sijunjung was very enthusiastic in welcoming the concept of independent learning. Teachers and observers of education at SMP Negeri 12 Sijunjung hope that the concept of independent learning that will be applied by the school will bring positive changes to the development of the quality of education at that school because this will help provide students with the skills needed in the 21st century. The results showed that, planning in the literacy-based independent learning program in science learning at SMP Negeri 12 Sijunjung was conducted by holding deliberations with various related elements. Planning lessons was carried out in the classroom, and outside, planning in learning was cnducted by carrying out a literacy movement that has 2 goals, namely general goals and specific goals. Planning constraints in the literacy-based independent learning program in science learning at SMP Negeri 12 Sijunjung consists of 3 obstacles, namely: 1). Lack of human resources who can understand literacy programs properly and correctly; 2) time for literacy activities at school; and 3) the school library is only limited to the school library, and the library collection only provides school books, very few other additional books.